2017
DOI: 10.5897/ijnm2017.0275
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual symptoms in young students and in their mothers at their ages

Abstract: Premenstrual symptoms are gradually becoming recognized socially and measures taken to cope with premenstrual symptoms are changing. The purpose of this study was to determine the differences in degree of recognition, in physical and emotional symptoms and in means for coping with premenstrual symptoms between nursing students and their mothers at the ages of the nursing students. This study was conducted between July and November, 2016. 272 nursing students and 272 mothers of the students were recruited. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…Although long-term prospective studies have not been carried out, we speculate that bad eating habits when young may lead to increased lifestyle-related diseases such as diabetes and hypertension at an older age. The prevalence of common psychological symptoms such as irritability, depression and anger before menstruation in the present study were similar to those previously reported in Japan (Takeda et al, 2006;Fukuoka et al, 2017). However, the prevalence of these symptoms may be different depending on the study conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although long-term prospective studies have not been carried out, we speculate that bad eating habits when young may lead to increased lifestyle-related diseases such as diabetes and hypertension at an older age. The prevalence of common psychological symptoms such as irritability, depression and anger before menstruation in the present study were similar to those previously reported in Japan (Takeda et al, 2006;Fukuoka et al, 2017). However, the prevalence of these symptoms may be different depending on the study conditions.…”
Section: Discussionsupporting
confidence: 90%
“…In Brazil, it was shown that the desire for foods rich in sugar, salt and fat was increased during the premenstrual period among university students (Souza et al, 2018). In Japan, 98% of nursing university students (mean age: 20.1 years) reported a desire for sweets and overeating as well as irritability and depression as the most frequent symptoms (Fukuoka et al, 2017). Another study showed that 64.6% of high school students aged 15-19 years suffered from premenstrual symptoms and that the prevalences of anxiety/tension, anger/irritability, and overeating/food cravings were high (Takeda et al, 2010).…”
Section: Introductionmentioning
confidence: 99%